Sitting Position in Neurosurgery - Goraksha, Shwetal; Thakore, Bhoomika; Monteiro, Joseph (Journal of Neuroanaesthesiology and Critical Care, 2019)
Neurosurgery in the sitting position is used for resection of tumors located in the cerebellopontine angle, pineal region, other technically difficult tumors in the infratentorial region, as well as surgeries of the cervical spine. Since its inception, the use of this particular position has been contentious due its risk-benefit analysis. With improved microsurgical equipment and surgical and anesthetic techniques, as well as advanced monitoring techniques to assure patient safety, many centers are revisiting the sitting position for its potential benefits.
Keywords: patent foramen ovale; sitting position; venous air embolism